MODEL OF MOVEMENT GENERATION AT SMKN-1 PALANGKA RAYA - Tamara Apriliayana; Tarita Aprilani Sitinjak; Samuel Layang (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2024)
Education is a primary need to be a necessity in creating prosperity and welfare of community life. There are traffic jams caused by the movement of generation in schools, one of which is the land use that causes generation at SMKN-1 Palangka Raya school on Tambun Bungai street in Palangka Raya City, the purpose of this study is to determine the model of movement generation at SMKN-1 Palangka Raya. Which later is expected to be used to estimate the number of people leaving the school in the future and as an anticipation of problems arising from the generation of travel. The research method uses a qualitative descriptive method by distributing questionnaires to respondents who do the generation at SMKN-1 Palangka Raya, with a total of 100 questionnaires distributed and school data. the results obtained. Using validity and reabelity instrument testing, correlation test with data analysis in the form of simple and multiple linear regression, t test, F test and coefficient of determination. The results of the analysis show that the most representative model for forecasting the generation of school movements of SMKN-1 Palangka Raya is Y 735.287 - 1.799 X2 + 7.658 X4 R2 of 0.783, where Y is the movement, X2 is the number of students, and X4 is the total number of teachers & employees. Factors that have a strong influence on the generation of movements at SMKN-1 Palangka Raya are the number of students (X2) and the total number of teachers & employees (X4).